Use of single-dose perioperative antimicrobial therapy is acceptable in recipients of living-donor renal transplants in the rituximab era. Issue 4 (April 2019) - Nishimura, Shingo; Wada, Koichiro; Araki, Motoo; Sadahira, Takuya; Maruyama, Yuki; Mitsui, Yosuke; Tanimoto, Ryuta; Kobayashi, Yasuyuki; Watanabe, Toyohiko; Nasu, Yasutomo
Abstract: Objective: The aim of this study was to evaluate the efficacy of single-dose perioperative antimicrobial therapy as infection prophylaxis in recipients of living-donor renal transplants in the rituximab era. Patients and methods: Between 2009 and 2017, 84 recipients underwent living-donor renal transplantation (LDRT) at Okayama University Hospital; 3 with vascular/urinary complications requiring additional surgery were excluded from this analysis. Data including recipient characteristics, antimicrobial prophylaxis and administration of rituximab were retrospectively examined for an association with perioperative infections. Prophylactic antimicrobial agents, selected according to the Results of preoperative urine cultures, were administered just before incision. Perioperative infections, which consisted of surgical site infections, remote infections, and urinary tract infections, were defined as a positive culture indicating required administration of additional antimicrobial agents. Results: Among the 81 recipients, prophylactic cefazolin, ampicillin/sulbactam, and others were administered to 66 (82%), 13 (16%), and 2 (3%) recipients, respectively. Twenty-one (26%) received single-dose antimicrobial prophylaxis, while 60 (74%) received multiple doses up to 7 days. Rituximab was used in 59 (72.8%) recipients. The incidence of urinary tract infection, surgical site infection and remote infection was 13 (16%), 1 (1%), and 0, respectively. Univariate analysis could not demonstrate any significant risk factors for postoperative urinary tract infections, including a single dose vs multiple doses of antimicrobial therapy ( P  = 0.069) and administration of rituximab ( P  = 0.717). Conclusions: Our data suggest that the use of single-dose perioperative antimicrobial therapy is acceptable for prophylaxis of infections in patients undergoing LDRT, even in the rituximab era.